A revision of the genus Puranoides moulton and description of two new species from Malaysia - Azman Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Puranoides klossi and Puranoides sphinx were reexamined and redescribed in this paper. A revision of the genus Puranoides from Malaysia has led to the discovery of two new species that need to be described as new to science namely Puranoides ismaili sp. nov. from Sabah and Puranoides schouteni sp. nov. from Johor and Pahang. Both species are differed from each other and located under the same species group.